Pengembangan dan Perancangan Alat Potong Sayur dengan Menggunakan Metode Quality Function Deployment (QFD): [Vegetable Cutting Tools Development and Design Using Quality Function Deployment (QFD) Method] - Fanny Limiyana; sylvia sylvia (Universitas Pelita Harapan, 2025)
Technology can help household chores. One household task involves manual cutting of vegetables. The concept of vegetable cutting tool’s design and development is driven by the need to reduce injuries and increase productivity for users. The research’s objective is to design and develop a vegetable cutting tool using the Quality Function Deployment (QFD) method. The limitations of the problems in QFD are the creation of the House of Quality , parts deployment, and product development and design is on phases 0, 1, 2, and 3. Phase 0 generates a mission statement for the vegetable cutting tool. Phase 1 creates assessments for the HoQ. Phase 2 produces design representations. Phase 3 designs the prototype. First step of HoQ is gathering feedback on customer needs based on feature, performance, and ergonomic aspects. The Voice of Customer results in six variable WHATs and seven HOWs. The HoQ shows three main priorities for product design and development: short user steps, blade sharpness, and automation of the tool. Parts deployment identifies critical components in the design of the tool, including the main frame, tool automation, and blade. Subsequently, the vegetables cutting tool’s prototype is designed. Prototype shows difference in ergonomic and shorter user step. Bahasa Indonesia Abstract: Teknologi dapat membantu manusia menyelesaikan pekerjaan rumah tangga. Salah satu pekerjaan rumah tangga yaitu pemotongan sayur yang manual. Gagasan pengembangan dan perancangan alat potong sayur dilandasi oleh kebutuhan pengurangan cedera serta meningkatkan produktivitas kerja bagi penggunanya. Tujuan dari penelitian ini yaitu untuk merancang dan mengembangkan produk alat potong sayur menggunakan metode Quality Function Deployment (QFD). Pembatasan masalah penelitian pada QFD dilakukan penyusunan House of Quality, parts deployment, serta pada pengembangan dan perancangan produk berfokus pada fase 0, 1, 2, dan 3. Fase 0 menghasilkan mission statement alat potong sayur. Fase 1 menghasilkan penilaian penyusunan HoQ. Fase 2 menghasilkan penggambaran desain. Fase 3 berfokus perancangan prototype. Penyusunan awal HoQ adalah mendapatkan suara kebutuhan pelanggan yang didasarkan aspek fitur, performansi dan ergonomi. Pengumpulan VoC menghasilkan enam variabel WHATs dan tujuh HOWs. Hasil HoQ mendapatkan tiga prioritas utama dalam pengembangan dan perancangan produk yaitu langkah penggunaan singkat, ketajaman pisau, dan otomatisasi alat potong sayur. Parts deployment mengidentifikasi komponen kritis dalam perancangan alat potong sayur yaitu kerangka utama, otomatisasi alat, dan pisau pemotong. Lalu, dilanjutkan perancangan prototype alat potong sayur. Prototype memberikan pengembangan yang terlihat pada aspek ergonomi dan langkah penggunaan alat singkat.